The Effect of Executive Diversification on CSR with Banking Performance an Intervening Variable - Ariska, Reza; Wijayanti, Indah Oktari (Transpublika Publisher, 2025)
The aim of this study is to investigate the impact of Executive Diversification on Corporate Social Responsibility (CSR) with banking performance as a mediator. The research will focus on data from banking firms that are listed on the IDX. The research will explore how executive traits (such as nationality, ethnicity, and gender) affect CSR, with banking performance acting as a mediating factor. The variables involved are Executive Citizenship, Executive Ethnicity, and Executive Gender. The study will use multiple linear regression to test the hypothesis, utilising panel data and E-Views 12 for analysis. The research findings suggest that executive traits, specifically citizenship, ethnicity, and gender, do not significantly influence CSR. The connection between executive traits such as citizenship and ethnicity and CSR through banking performance cannot be proven using banking performance as a mediator. However, when it comes to executive traits based on gender, banking performance can demonstrate the impact of gender on CSR. Executive traits related to citizenship, ethnicity, and gender all play a role in influencing CSR through banking performance.